Expression cloning of a reserpine-sensitive vesicular monoamine transporter. - Erickson, J D (1992)
A cDNA for a rat vesicular monoamine transporter, designated MAT, was isolated by expression cloning in a mammalian cell line (CV-1). The cDNA sequence predicts a protein of 515 amino acids with 12 putative membrane-spanning domains. The characteristics of [3H]serotonin accumulation by CV-1 cells expressing the cDNA clone suggested sequestration by an intracellular compartment. In cells permeabilized with digitonin, uptake was ATP dependent with an apparent Km of 1.3 microM. Uptake was abolished by the proton-translocating ionophore carbonylcyanide p-trifluoromethoxyphenylhydrazone and with tri-(n-butyl)tin, an inhibitor of the vacuolar H(+)-ATPase. The rank order of potency to inhibit uptake was reserpine > tetrabenazine > serotonin > dopamine > norepinephrine > epinephrine. Direct comparison of [3H]monoamine uptake indicated that serotonin was the preferred substrate. Photolabeling of membranes prepared from CV-1 cells expressing MAT with 7-azido-8-[125I]iodoketanserin revealed a predominant tetrabenazine-sensitive photolabeled glycoprotein with an apparent molecular mass of approximately 75 kDa. The mRNA that encodes MAT was present specifically in monoamine-containing cells of the locus coeruleus, substantia nigra, and raphe nucleus of rat brain, each of which expresses a unique plasma membrane reuptake transporter. The MAT cDNA clone defines a vesicular monoamine transporter representing a distinct class of neurotransmitter transport molecules.